Analisis kuat tekan dan penyerapan air batu bata ditinjau dari berbagai lama pembakaran - T, Panennungi; Rauf, Bakhrani A. Rauf A. (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2023)
This research aims to describe: compressive strength of M-5a module, water absorption, and  compressive strength difference 7, 9, and 11 days furnace duration. The methods are: making brick which is composed by 1 of rice husk and 3 of clay to 120 bricks, dehydrating on sunlight for 7 days, then going furnace for 7, 9, and 11 days, examining to compressive strength and  water absorption each 20 bricks of 7, 9, and 11 days furnace. The result: average of compressive strength of M-5a module 7 days furnace is 35,80 kg/cm2, 9 days is 37,30 kg/cm2, 11 days is 39,30 kg/cm2,  average of water absorption  of M-5a module 7 days furnace is 22,96 %, 9 days is 21,50 %, and 11 days is 19,25 %, and no significant difference on compressive strength average amongs module of M-5a on 7 days, 9 days, and 11 days furnace duration.